Influence of β2-Glycoprotein-l Upon the Content of cAMP and cGMP in Human Blood Platelets - Nimpf, Johannes; Gries, Anni; Wurm, Helmut; Kostner, Gerhard M (Thrombosis and Haemostasis, 1985)
The influence of β2-glycoprotein-I on the cyclic nucleotide content in human gel filtered platelets (GFP) was studied: 1) β2-G-I up to a concentration of 5 mg/ml does not alter the basal cAMP level in resting GFP and also does not influence the action of PGE1 which strongly inhibits platelet aggregation by elevation of cAMP.2) Collagen induced aggregation of GFP leads to an increase of the platelet cGMP content. Preincubation of GFP with 0.2 mg/ml of β2-G-I enhances significantly the cGMP increase by collagen.3) In a similar manner β2-G-I also amplifies the increase in cGMP concentration induced by ADP. In this case, a concomitant alteration of the aggregation pattern is observed.4) Thrombin produces a much higher cGMP elevation in GFP than ADP or collagen. The admixture of 0.2 mg/ml of β2-G-I is not able to enhance further the thrombin effect on cGMP. The results are discussed in view of the possible significance of these observations for platelet aggregation in vivo.
Keywords: β2-glycoprotein-I; cAMP; cGMP; Platelet aggregation